CONTEMPORARY ISLAMIC EDUCATIONAL LEADERSHIP - Chepi Rafiudin; Levia Inggrit Sayekti; Encep Syarifudin (Sean Institute, 2023)
Leadership is the ability to influence other people, subordinates or groups, has special expertise in a specific field to achieve organizational goals or a group. While educational leadership is an ability and process of influencing, guiding, coordinating, and mobilizing other people who are related to the development of education and the implementation of education and teaching, so that the activities carried out can be more efficient and effective in achieving educational goals and teaching. Leaders have the power to regulate their members but the power given must be used responsibly. Responsible means not to use the powers that have been given for the benefit of himself or the individual, not authoritarian or all decisions must be based on his decision but not the result of the deliberations of its members